ON THE PROBLEM OF DEFINITION OF CRITERIA, LEVELS AND INDICATORS OF ENVIRONMENTAL CONSCIOUSNESS FUTURE TEACHERS OF BIOLOGY (Pedagogy of Higher and Secondary Education, 2022)
In article examines the problem of criteria, stages and indices of perspective Biology teachers' ecological consciousness.